MNEMONIC TECHNIQUES OF LEARNING A FOREIGN LANGUAGE IN HIGHER EDUCATION - Baranenkova, Natalia A.; Svetenok, Liudmyla K. (Educological discourse, 2016)
The article deals with the problems of using the principles of mnemonics to achieve communication goals and improve speech competence of students of technical universities during English classes. An attempt to classify and establish patterns of functioning of mnemonic techniques were made, the benefits of their use to enhance vocabulary were tried to be highlighted. The conditions under which the use of mnemonic techniques makes interpreting as effective as possible were defined; the basic techniques were highlighted and illustrated. The advantages and disadvantages of each technique were analyzed, and some recommendations on their use in teaching students to interpret and communicate in a foreign language environment were provided.